Father Migration and Mother Migration: Different Implications for Social, School, and Psychological Adjustment of Left-Behind Children in Rural China. Issue 120 (2nd November 2019) - Chen, Xinyin; Li, Dan; Liu, Junsheng; Fu, Rui; Liu, Shihong
ABSTRACT: This study examined the relations between parental migration and the adjustment of left-behind children and the mediating role of parental support in rural China. Data were collected for 4, 429 students (2, 229 boys, M age = 12 years) in public schools from peer evaluations, teacher ratings, self-reports, and school records. The analyses revealed different patterns of relations of mother migration and father migration to children's adjustment. Whereas mother migration was negatively associated with children's social competence and academic achievement and positively associated with children's psychological problems, father migration was positively associated with children's positive adjustment, mainly through the mediation of maternal support. The results concerning the different implications of father migration and mother migration for children's adjustment and the critical role of maternal support represent a significant contribution to the understanding of human development in the contemporary rural Chinese context. The results are also useful for policy-makers and professionals to develop programs and strategies to help rural left-behind children in China.